Mechanosensitive Ion Channel Piezo1 Regulates Diet-Induced Adipose Inflammation and Systemic Insulin Resistance - Zhao, Can; Sun, Qiushi; Tang, Lingyi; Cao, Yang; Nourse, Jamison L.; Pathak, Medha M.; Lu, Xiang; Yang, Qin (Frontiers in Endocrinology, 2019)
Adipocytes function as an energy buffer and undergo significant size and volume changes in response to nutritional cues. This adipocyte plasticity is important for systemic lipid metabolism and insulin sensitivity. Accompanying the adipocyte size and volume changes, the mechanical pressure against cell membrane also changes. However, the role that mechanical pressure plays in lipid metabolism and insulin sensitivity remains to be elucidated. Here we show that Piezo1, a mechanically-activated cation channel stimulated by membrane tension and stretch, was highly expressed in adipocytes. Adipose Piezo1 expression was increased in obese mice. Adipose-specific piezo1 knockout mice (adipose-Piezo1-/-) developed insulin resistance, especially when challenged with a high-fat diet (HFD). Perigonadal white adipose tissue (pgWAT) weight was reduced while pro-inflammatory and lipolysis genes were increased in the pgWAT of HFD-fed adipose-Piezo1-/- mice. The adipose-Piezo1-/- mice also developed hepatic steatosis with elevated expression of fatty acid synthesis genes. In cultured adipocytes. Piezo1 activation decreased, while Piezo1 inhibition elevated pro-inflammatory gene expression. TLR4 antagonist TAK-242 abolished adipocyte inflammation induced by Piezo1 inhibition. Thus, adipose Piezo1 may serve as an adaptive mechanism for adipocyte plasticity restraining pro-inflammatory response in obesity.